PERLINDUNGAN HUKUM TERHADAP TANAH WAKAF DI INDONESIA: STUDI DALAM PERSPEKTIF HUKUM AGRARIA DAN PERADILAN AGAMA - Suni, Alif Afdillah; Saleha, Alifia Mumtazati; Abdurrahman, Faris (STAI Darul Qalam Tangerang, 2025)
Land waqf, which is a religious instrument that has deep social and economic significance in Indonesia, functions as a pillar of the welfare of the people and charity. However, its existence is very vulnerable to legal disputes, especially due to the massive practice of waqf that is not accompanied by legal-formal evidence. This study aims to comprehensively analyze the effectiveness of legal protection for waqf land through synchronization between the agrarian law regime and national waqf law. Using a juridical-normative research method enriched with a case study approach of jurisprudence, this study examines the interaction of laws and regulations, asset legalization mechanisms, and the role of judicial institutions. Key findings suggest that although the existing normative legal framework through the Basic Agrarian Law and the Waqf Law has provided a strong foundation for protection, the implementation of land registration as an absolute requirement of legal protection still faces significant sociological, cultural, and bureaucratic barriers. This gap between das sollen (aspired law) and das sein (reality in society) makes the crucial role of the Religious Court as the last bastion in providing substantive justice and legal certainty for administratively defective waqf assets. It was concluded that complete legal protection can only be achieved through strategic synergy between bureaucratic reform of land registration, strengthening of Nazhir's professional capacity, massive socialization of the law, and progressive law enforcement by the Religious Courts.